2018
DOI: 10.1245/s10434-018-6369-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery Plus Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Metastases From a Small Bowel Adenocarcinoma: Multi-Institutional Experience

Abstract: BackgroundThe multi-institutional registry in this study evaluated the outcome after cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) for patients with peritoneal metastases (PM) from small bowel adenocarcinoma (SBA).MethodsA multi-institutional data registry including 152 patients with PM from SBA was established. The primary end point was overall survival (OS) after CRS plus HIPEC.ResultsBetween 1989 and 2016, 152 patients from 21 institutions received a treatment of CRS plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Recently, another retrospective research enrolled 34 stage IV SBA patients with surgery, and the median OS and RFS were 28.6 and 18.7 months respectively 12 . Consistent with former studies, 11,12 we found that surgery was an independent factor associated with better survival for stage IV SBA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recently, another retrospective research enrolled 34 stage IV SBA patients with surgery, and the median OS and RFS were 28.6 and 18.7 months respectively 12 . Consistent with former studies, 11,12 we found that surgery was an independent factor associated with better survival for stage IV SBA.…”
Section: Discussionsupporting
confidence: 87%
“…152 stage IV SBA patients with peritoneal metastases were enrolled in a restrospective study in 2018, prolonged survival have been archived using combined treatment strategy of cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy (median OS was 32 months with survival rates of 46.4% at 3 years). Multivariate analysis revealed that absence of lymph node metastasis, well‐differentiated tumor, and peritoneal cancer index of 15 or lower were factors independently associated with improved OS 11 . Recently, another retrospective research enrolled 34 stage IV SBA patients with surgery, and the median OS and RFS were 28.6 and 18.7 months respectively 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is the most commonly used treatment for small bowel tumors 2,15 , and adjuvant chemotherapy has also been shown to play a role in improving the survival outcome of patients 16 .Up to now, the therapeutic effect of LND is still discussed controversially. From 2004 to the present, the number of lymph node dissections used in small bowel tumor resection has increased slightly, but the proportion of lymph node dissection and extended lymph node dissection have not changed signi cantly (Figure S2-3).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of residual tumor tissue following surgery is directly related to patient survival outcomes [10][11][12]. For this reason, the aim of surgery is the removal of all neoplastic foci during the cytoreductive procedure, and the standard approach is to achieve no gross residual disease (NGR) [13].…”
Section: Introductionmentioning
confidence: 99%